Tattooed Bodies Theorizing Body Inscription Across Disciplines and Cultures - Martell, James; Larsen, Erik. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"Tattooed Bodies-apart from often being an exemplary model of Continental philosophy-is a groundbreaking contribution to tattoo studies that shows us how tattooing, when taken seriously, can open up the meanings of works of art, literature, film, and theory itself in unexpected ways. For those who have already been thinking about the meaning of "the tattoo," this collection of essays will greatly expand possibilities of inquiry. For those who are new to the field, several essays act simply as excellent primers on how to undertake deconstructive, anthropological, aesthetic analysis in general offering up scholarly, nuanced investigations of texts without indulging in exclusionary jargon." -Danielle Meijer, DePaul University "What is a tattoo? Associated in the past with criminals and degenerates, tattoos have become high fashion in the 21st century. In this collection, leading scholars speculate about the nature and implications of these bodily inscriptions. Are they social or antisocial? Conformist or rebellious? Decorative or disfiguring? Atavistic or futuristic? How do they relate to other scars, such as the navel as the mark of our maternal origin? By opening up these questions and many more, the essays in this volume show how the tattoo challenges the distinction between word and flesh, self and society, life and death." -Maud Ellmann, University of Chicago The essays collected in Tattooed Bodies draw on a range of theoretical paradigms and empirical knowledge to investigate tattoos, tattooing, and our complex relations with marks on skin. Engaging with perspectives in art history, continental philosophy, media studies, psychoanalysis, critical theory, literary studies, biopolitics, and cultural anthropology, the volume reflects the diversity of meanings attributed to tattoos across cultures. Essays explore tattoos and tattooing in Derrida, Deleuze and Guattari, Lacan, Agamben, and Jean-Luc Nancy, while interpreting tattoos in literary works by Melville, Beckett, Kafka, Genet, and Jeff VanderMeer, among others. James Martell is Associate Professor of French at Lyon College, USA. Erik Larsen is Assistant Professor of Medical Humanities at the University of Rochester, USA.
Chapter 1: Introduction: "Totem and Tattoo" -- Part I: TATTOOING (AS) ART -- Chapter 2: "A Medium, Not a Phenomenon: An Argument for An Art Historical Approach to Western Tattooing" -- Chapter 3: "Contemporary Western Tattooing as an Inherently Collaborative Practice: The Contingent Authorial Input and Operational Mode of the Tattooist" -- Chapter 4: "Branch out, Perform, Interlink: Reading Tattoos as Soma-Hypertexts in Shelley Jackson's SKIN and Skin Motion's Soundwave Tattoos" -- Part II: TRANSCULTURAL TATTOOING -- Chapter 5: "Hüh tu pu/ To Mark with Tattoo: Chen Naga Tiger-Spirit Tattoos and Indigenous Ontologies in Northeast India" -- Chapter 6: "The last generation of tattooed Bedouin women in southern Jordan: When tradition and climate change collided in Wadi Rum" -- Chapter 7: "Tattoos, 'Tattoos,' Vikings, 'Vikings,' and Vikings" -- Part III: TATTOOING THE POLITICAL BODY -- Chapter 8: "Herman Melville's (Un)Readables: Tattoos" -- Chapter 9: "The Life of the Tattoo: Subcutaneous Surveillances and the Economy of the Stigmatization" -- Chapter 10: "Democratic Hieroglyphs: On the People's Indecipherable Flesh in Moby-Dick" -- Part IV: TATTOOING LITERATURES -- Chapter 11: "Jeff VanderMeer's Southern Reach Trilogy: Writing Out the Body Between Grammatology and Exscription" -- Chapter 12: "Tattooing Terminable Interminable: Psychoanalysis, Corporeal Marking and Literature" -- Chapter 13: "Effluvial Exhalations: Genet's ontological quandary" -- Chapter 14: "Limited Ink: Of Repressence, Inkorporation, and Marineation" -- Chapter 15: "Derrida & Deleuze as Tattooed Savages".
Keywords: Clothing and dress-Social aspects; Human body in popular culture; Culture-Study and teaching; Arts; Fashion and the Body; Cultural Studies; Visual Culture; Arts